E-learning and the science of instruction : proven guidelines for consumers and designers of multimedia learning - Clark, Ruth Colvin; Mayer, Richard E., 1947- (Wiley, 2024)
"This edition includes 3 new chapters focused on evidence regarding signaling in e-Learning, video-based instruction, and immersive virtual reality platforms. The 21 chapters summarized in the table that follows are grouped into five sections. You may choose to read the chapters in order or if you have special interests such as evidence on online games or immersive virtual reality, you can jump to those chapters. Chapters 1-3 summarize foundational concepts that form the base for the rest of the book including the science of learning and basics of experimental evidence. We recommend you start with these chapters. In Section 2, we offer 6 chapters with guidelines and evidence regarding optimal use of visuals, text, and audio in e-learning. Evidence on how to promote productive engagement in e-learning is the focus of Section 3. Section 4 includes 2 chapters relevant to organizational decisions you can make in design and sequencing of lessons and courses. We review social cues in e-learning in Section 5 including personalization of your lessons and ways to promote productive collaborative learning. Section 6 includes 4 chapters highlighting evidence on special applications of digital learning including simulations, games, video-based instruction, and immersive platforms. Chapter 21 includes a checklist that summarizes all of the guidelines presented throughout the book. That is a good place to help you put together all you have learned"--